iOS Swift programming by example : LiveLessons - Miller, BJ (Computer software developer); Safari eBooks ([Place of publication not identified] : Addison-Wesley Professional, 2015)
"The video starts with a comprehensive survey of Swift fundamentals, including how to work with Playgrounds, Apple's interactive coding environment, how to declare constants and variables, how to create iterating code with loops, and much more. Next, the training teaches viewers how to work with functions and closures, define data structures, perform actions using Methods, work with UIKit, write Swift code that interacts with Objective-C, and design interfaces using storyboards. The video further covers more advanced Swift topics such as using the map/reduce/filter functions and adding behavior to existing data types with generics. After watching this video, developers who perhaps have never worked with a functional programming language will understand the differences between Swift and Objective-C, current iOS developers will gain a better understanding of how to incorporate Swift into their application programming practices, and new iOS developers will learn how Swift simplifies the process of building their first (or second) iOS application."--Resource description page.
Title from resource description page (viewed April 28, 2015)
Date of publication taken from resource description page.
Presenter, BJ Miller.
Keywords: iOS (Electronic resource); iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; Electronic books